A New Approach for Solving Fuzzy Cooperative Continuous Static Games - Edalatpanah, Seyyed Ahmad; Abd El- Wahed Khalifa , Hamiden; Keyser, Robert S. (Soft Computing Fusion with Applications, 2024)
This study explores Cooperative Continuous Static Games (CCSGs) characterized by fuzzy cost functions that are piecewise quadratic. It introduces an effective approximation technique, specifically the close interval approximation for Piecewise Quadratic Fuzzy Numbers (PQFNs). The paper employs the weighted Tchebycheff method to derive an optimal compromise solution and establishes the corresponding stability set of the first kind. Additionally, a numerical example is provided to illustrate the effectiveness of the proposed method in computational terms.